2022
DOI: 10.3390/horticulturae8060479
|View full text |Cite
|
Sign up to set email alerts
|

Biotransforming the Spent Substrate of Shiitake Mushroom (Lentinula edodes Berk.): A Synergistic Approach to Biogas Production and Tomato (Solanum lycopersicum L.) Fertilization

Abstract: Agro-wastes, such as crop residues, leaf litter, and sawdust, are major contributors to global greenhouse gas emissions, and consequently a major concern for climate change. Nowadays, mushroom cultivation has appeared as an emerging agribusiness that helps in the sustainable management of agro-wastes. However, partial utilization of agro-wastes by mushrooms results in the generation of a significant quantity of spent mushroom substrates (SMS) that have continued to become an environmental problem. In particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 43 publications
2
20
0
Order By: Relevance
“…Moreover, the presence of MC2 in the media may provide more readily available nutrients for the plants compared to MC1. In support of this, higher levels of nutrients including N, C, P, Ca have been reported in Shiitake mushroom compost compared to White oyster mushroom compost by Hernández et al 18 and Kumar et al 29 In addition, PCA results suggested that growing media made from MC2 were better for the improvement of plant growth and yield performance in all tested microgreens (Figure 4). In agreement with our results, it previously shown that application of mushroom compost enhanced germination rate and seedling growth in cucumber and lettuce plants.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Moreover, the presence of MC2 in the media may provide more readily available nutrients for the plants compared to MC1. In support of this, higher levels of nutrients including N, C, P, Ca have been reported in Shiitake mushroom compost compared to White oyster mushroom compost by Hernández et al 18 and Kumar et al 29 In addition, PCA results suggested that growing media made from MC2 were better for the improvement of plant growth and yield performance in all tested microgreens (Figure 4). In agreement with our results, it previously shown that application of mushroom compost enhanced germination rate and seedling growth in cucumber and lettuce plants.…”
Section: Discussionsupporting
confidence: 63%
“…DOI: 10.15406/hij.2022.06.00263 nutrients for plants that may explain the observed higher germination and plant height in these media. 29 PCA analysis results validated T4 and T5 enhancement of microgreens plant performance compared to other treatments (Figure 2). As a result, T4 and T5 were selected for further investigation in the Experiment 2.…”
Section: Discussionmentioning
confidence: 52%
“…Increased salinity causes osmotic stress and ion imbalance, as well as oxidative stress and metabolic abnormalities [30], thus, causing stunted growth. Herrera et al [31] reported that the excess of soluble salts in municipal solid waste compost used at doses higher than 30% in growing media lowered the development of tomato seedlings. Similarly, Kumar et al [32], studying the effect of spent mushrooms digestate with a slightly high EC value on tomato germination, noted a decrease in seed germination and seedling stem and root length overcoming the optimal dilution of 10%.…”
Section: Phytostimulantmentioning
confidence: 99%
“…A compost addition of up to 30% in growing media has been reported to improve total pore space and organic matter content, promoting root development [43]. Moreover, compost nutrients and phytohormones induce root tip proliferation, improving root volume [31]. Similar to the effect reported for compost addition, the use of biochar in growing media increases root length and amount of root air, leading to an extension of root surface area and, consequently, to an increased capacity of water and nutrient absorption [44].…”
Section: Plant Developmentmentioning
confidence: 99%
“…Recently, Huang et al reported the preparation of a liquid organic fertilizer (LOF) using Hypsizygus marmoreus MSM and the evaluation of its efficiency in the cultivation of pak choi. Similarly, Kumar et al reported the biotransformation of Lentinula edodes MSM into biogas and the utilization of the slurry digestate as a fertilizer in tomato (Solanum lycopersicum L.) crop.…”
Section: Introductionmentioning
confidence: 99%